(untitled) (The International Journal for Scientific Research, 2025)
The study was conducted on a part of the Samawah desert soil located in the southern part of AL-Muthanna Governorate, with the aim of studying the distribution status of contamination with uranium, focusing on its environmental and health impacts, and to analyze uranium concentrations in soil samples. It started reviews the methods of soil pollution in general, addressing how uranium enters the environment due to human activities such as mining and the use of depleted uranium, in addition to the geological factors that affect the concentration of uranium in the soil. Samples were collected from different locations in the region, and the results showed variations in uranium concentrations between samples. Uranium concentrations ranged between 0.00003% and 0.00279%, with some samples, such as the sample, exceedingS31 registered (27.9 ppm) parts per million), which far exceeds the expected natural limits for uranium concentrations in soil. And when comparing results with global environmental standards, such as those set by the World Health Organization (WHO) and the U.S. Environmental Protection Agency (EPA) found that many samples exceeded normal levels, indicating environmental contamination. In particular, samples containing elevated uranium concentrations are indicative of an unnatural source of contamination, such as industrial waste or military activities. That The potential environmental and health impacts of this contamination include contamination of groundwater and surface water, which can cause serious health problems such as kidney damage when contaminated water is consumed. Exposure to uranium in soil can also negatively impact plants and crops, potentially leading to reduced agricultural productivity.